2010
DOI: 10.1016/j.virol.2010.08.027
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the receptor binding site enhances infectivity of 2009 H1N1 influenza hemagglutinin pseudotypes without changing antigenicity

Abstract: The 2009 H1N1 pandemic highlights the need to better understand influenza A infectivity and antigenicity. Relative to other recent seasonal H1N1 influenza strains, the 2009 H1N1 virus grew less efficiently in eggs, which hindered efforts to rapidly supply vaccine. Using lentiviral pseudotypes bearing influenza hemagglutinin (HA-pseudotypes) we evaluated a glutamine to arginine mutation at position 223 (Q223R) and glycosylation at residue 276 in HA for their effects on infectivity and neutralization. Q223R emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…It is of considerable importance to detect new antigenic changes occurring in HA protein when updating vaccine compositions. The results of our study are consistent with the results of others in terms of changes in number and location of glycosylation sites (20,21), mutations/conservation in important positions such as Q240R (22), V169T, and D239G (24,25), changes/conservation in active/binding sites (23,24), and conservation in important domains such as fusion peptide (24,25). Evaluation of changes in predicted ligandbinding sites, type and number of ligands was done in our study, which indicated a significant change in ligand binding site of 2009 isolates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is of considerable importance to detect new antigenic changes occurring in HA protein when updating vaccine compositions. The results of our study are consistent with the results of others in terms of changes in number and location of glycosylation sites (20,21), mutations/conservation in important positions such as Q240R (22), V169T, and D239G (24,25), changes/conservation in active/binding sites (23,24), and conservation in important domains such as fusion peptide (24,25). Evaluation of changes in predicted ligandbinding sites, type and number of ligands was done in our study, which indicated a significant change in ligand binding site of 2009 isolates.…”
Section: Discussionsupporting
confidence: 93%
“…Addition of glycans to the HA is an important mechanism contributing to antigenic drift and therefore sustained circulation of influenza A virus in the human population (20,21). The (Table 3), in which some changes (creation/ deletion of glycosyla- Position 240, which is located in receptor binding site, is one of the important positions in HA (22). This position is conserved in sequences of 2006 to 2008 isolates, yet, from 2009 onwards, Q240R mutation has occurred in some isolates.…”
Section: Resultsmentioning
confidence: 99%
“…As previously described (22), the full-length Q223R HA open reading frame (ORF) from A/Mexico/4108/2009 (MX HA) (GenBank accession no. GQ223112), which was previously reported to enhance pseudovirus infectivity (18), and the wild-type NA ORF from A/California/04/2009 (GenBank accession no. FJ966084) were amplified from the respective viruses by reverse transcription-PCR (RT-PCR) and placed into the CMV/R 8B expression plasmid, encoding HA from A/PR/8/34 (PR HA) (GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that the M2 protein enhanced (H1N1) pdm09 HA-pseudovirus infectivity when M2 was coexpressed with HA during pseudovirus production (18). However, the mechanism responsible for this effect remained unknown.…”
mentioning
confidence: 99%
“…An egg adaptation mutation leading to a Q223R substitution in HA was found to have occurred in the passaged viruses encoding both wild-type PB1 and PB1-V43I. The Q223R mutation in the receptor binding site improves infectivity in egg and in human cells without changing HA antigenicity (28,35). Interestingly, the K154N and G155E antigenic mutations were introduced into the HA of the PB1 wild-type vaccine virus following passages; however, these mutations were not found in the PB1-V43I vaccine strain (Tables 3 and 4).…”
Section: Discussionmentioning
confidence: 99%